Pengaruh Variasi Pakan Bekatul Suplementasi Daun Pepaya (Carica papaya L.) terhadap Berat Badan dan Karakteristik Ukuran Tubuh Ayam (Gallus domesticus) - Cindyana Putri Puspita Hapsari; Baskoro Adi Prayitno; Meti Indrowati (Habitat: Jurnal ilmiah ilmu Hewani dan Peternakan, 2024)
This study evaluated the impact of papaya leaf (Carica papaya L.) supplementation in bran feed on body weight and body size of chickens (Gallus domesticus). Three groups of chickens were fed with papaya leaf flour supplementation to see the efficiency on chicken growth. This study was conducted for 28 days at the "Rinael Farm" Farm, Pulerejo Village, Manggis, Mojosongo, Boyolali, Central Java. This study was implemented through an experimental method with a Completely Randomized Design (CRD) design that included three treatments and three repetitions: P0 (no supplementation), P1 (10% supplementation), and P2 (20% supplementation). The results of the study proved that 10% and 20% papaya leaf supplementation did not have a significant effect on chicken weight (P> 0.05). However, papaya leaf supplementation had a significant impact on the characteristics of chicken body size, with a p value <0.001. Papaya leaf supplementation increased chicken body size, with group P1 experiencing the most significant and consistent increase, while group P2 showed greater variation in growth. Supplementation with 10% papaya leaves (P1) proved to be the most effective in increasing chicken growth efficiency.